Pulse wave amplitude drops during sleep: clinical significance and characteristics in a general population sample. Issue 7 (24th January 2020) - Hirotsu, Camila; Betta, Monica; Bernardi, Giulio; Marques-Vidal, Pedro; Vollenweider, Peter; Waeber, Gérard; Pichot, Vincent; Roche, Frederic; Siclari, Francesca; Haba-Rubio, Jose; Heinzer, Raphael
Abstract: Study Objectives: To explore the clinical significance of pulse wave amplitude (PWA)-drops during sleep as a biomarker for cardiometabolic disorders and describe their main characteristics in a general population sample. Methods: Cross-sectional study of HypnoLaus cohort, in which 2162 individuals underwent clinical assessment and in-home full polysomnography. PWA-drops were derived from photoplethysmography and processed using a validated automated algorithm. Associations between PWA-drop features (index, mean duration, and mean area under the curve [AUC]) with hypertension, diabetes, and previous cardiovascular (CV) event were analyzed using multivariable-adjusted logistic regression. Results: Two thousand one hundred forty-nine participants (59 ± 11 years, 51% women, 9.9% diabetes, 41.3% hypertension, 4.4% CV event) were included. Mean ± standard deviation ( SD ) of PWA-drop index, duration, and AUC during sleep were 51.0 ± 20.3 events/hour, 14.0 ± 2.7 seconds, and 527±115 %seconds, respectively. PWA-drop index was lower in women and decreased with age, while its mean duration and AUC increased in men and elderly. Overall, lower PWA-drop index, longer duration and greater AUC were associated with increased odds of hypertension, diabetes, or CV event after adjustment for confounders. Participants in the lowest quartile of mean duration-normalized PWA-drop index had a significantly higher odds ratio (OR) of hypertension (OR = 1.60 [1.19–2.16]), CV event (OR = 3.26 [1.33–8.03]), and diabetes (OR = 1.71 [1.06–2.76]) compared to those in the highest quartile. Similar results were observed for mean AUC-normalized PWA-drop index regarding hypertension (OR = 1.59 [1.19–2.13]), CV event (OR = 2.45 [1.14–5.26]) and diabetes (OR = 1.76 [1.10–2.83]). Conclusions: PWA-drop features during sleep seem to be an interesting biomarker independently associated with cardiometabolic outcomes in the general population.